A manifestação da vontade da criança na disputa judicial da guarda: escuta psicanalítica - Ferreira, Maria Teresa Fernandes (2008)
Currently, in custody disputes, the child has the right to be heard and to have its opinion considered, according to its age and maturity. The psychologist/psychoanalyst who works in the Family Court is required to produce a Report with the purpose of helping the Court´s decision. The present research aims to discuss and to find guiding principles for the hearing of the declaration of the child´s will in a custody dispute by its parents, from a psychoanalytical perspective. The case of a nine year old girl that affirmed in Court the desire of living with the mother and seeing the father only once a year is the starting point of this theoretical research over the psychoanalytic fundaments of the hearing of the case, how it appeared in that experience and how it was reflected in the report. Throughout this work, the peculiarities of psychoanalysis as a way of understanding the subject and the conditions that must be observed so that a sctrictu sensu analytic hearing is possible are studied. Then we present a reflection of the case, in the light of the theories studied, verifying that we could observe in the experience: i) the assumption of a subject of the unconscious, divided and desire full that constitutes itself from the oedipic structuration, that leads to the difference between speech and speak; ii) the concept of the child as having a sexuality of its own; iii) a hearing based on the ethic principles of psychoanalysis and the analysts'' formation. In the final considerations, we state that the institutional demand of a meaning for the case is a great difficulty for the analyst since he works from a place of 'not-knowing"